Influence of Pacific Decadal Oscillation on global precipitation extremes - Wenguang Wei; Zhongwei Yan; Zhen Li (Environmental Research Letters, 2021)
While the influence of the Pacific Decadal Oscillation (PDO) on precipitation has been extensively studied, its influence on precipitation extremes remains not well-known. Based on a series of generalized extreme value modeling experiments, this paper demonstrates some distinct regional patterns of the PDO’s influence on precipitation extremes worldwide. In eastern China, the well-known ‘southern flood (drought) and northern drought (flood)’ pattern in summer corresponds well to the positive (negative) phase of the PDO. In Australia, there tends to be a tripole pattern, with positive correlation between precipitation extremes and the PDO in the central region, and negative correlation in both eastern and western Australia. The precipitation extremes in northwestern Europe and western Russia roughly hold positive correlation with the PDO. These regional patterns of the PDO’s influences are explained via comparative analyses of the atmospheric circulation conditions between cold and warm PDO phases. Certain precipitation extremes tend to be missed or happen more than once during different phases of the PDO at more than 2/3 of stations in a typical region. The cold phase tends to exert more consistent influences than the warm phase in these typical regions. These findings not only indicate different risks of extreme precipitation for the typical regions during different phases of the PDO, but also have important implications for the near-term projection of variable regional climate extremes under global warming.